Rescuing the future: bequeathed misperception in international relations - Mehta, Jagat.S. (New Delhi, 2008)
This book is personal and academic essays, on Nehru, cold war and US, fresh water diplomacy, India-Nepal, India--Pakistan, Kashmir. global issues, nuclear and social justice
Keywords: Cultural exchange